Power system study for oil and gas platform connected to onshore grid / Rosshidi Hezrimi Taharim - Rosshidi Hezrimi, Taharim (2020)
Normally for oil and gas offshore platform, the electrical power supply is generated from the generator either using gas turbine generator, gas engine generator and diesel engine generator. The main power supply is backup by diesel engine generator in case emergency or during black start of the platform. As the design of oil and gas platform become complex, the size of generator keeps increasing. A new concept is being explored to mitigate this problem. Oil and gas company is looking to provide power generation from onshore and supplying the electrical power to a substation platform offshore and then distributed it to various platform. Even though the idea is feasible, but there is a challenge technically. One of the technical expect that need to be carefully consider is the Ferranti effect over long transmission line, in this case the submarine cable. Therefore, some study needs to be done to analyze the stability of the power system when a system is connected to long submarine cable. When there is long transmission line, the tendency of Ferranti effect to occur is likely. So, this study is performed to study the magnitude of Ferranti effect on the propose system and how to mitigate this power stability issue. A load flow study is perform using ETAP software to determine the effect of Ferranti Effect on difference length of submarine cable. Shunt reactor is used as the mitigation method to the Ferranti Effect. This study also determined the size of shunt reactor required over the length of submarine cable. Short circuit study was performed to determine the short circuit level at the receiving end for different length of submarine cable. This short circuit level is crucial in determined the rating of switchgear at the offshore.